Shifts in Indonesian-French Poem Translation - Widiastuti, Ni Made Ayu; Savitri, Putu Weddha (Lingual Journal of Language and Culture; Vol 2 No 2 (2016)DO - 10.24843/LJLC.2016.v02.i02.p05, 2016)
This paper aims at analyzing the translation shifts of a poem containing figurative expressions from Indonesian into French and describing the translation principles occur in the shifts. The data in this paper is an Indonesian poem with the title “Gestural Tubuh Perempuan” and its translation in French. This is a library research with qualitative-descriptive method. The analyses were conducted by applying translation shifts theory by Catford in Venuti (2000) and translation principles by Nida (1975). The findings show that there are many shifts occur in the target language. The shifts that frequently occur are in the intra-system of the language. There is only a few loss and skewing of information in the shifts, but a lot of addition of information especially for the use of French articles.
Keywords: poem, figurative expressions, translation shifts, translation principles